Editorial - Quintero Polo, Álvaro Hernán (Colombian Applied Linguistics Journal, 2007)
I would like to thank Dr. Amparo Clavijo Olarte, Director of the Colombian Applied Linguistics Journal, for the invitation to write this editorial. I am very pleased to start the presentation of the ninth issue by sharing with you all the result of the collaborative effort of the Editorial Committee and a group of twenty five national and international article evaluators. We would like to welcome Sarah Hudelson from Arizona State University, Janeth Velasquez, Judith Castellanos, and Luz Mary Quintero from Universidad Distrital Francisco José de Caldas; and Luz Dary Arias from Universidad Pedagógica Nacional as new members of the Editorial Review Board.